FUTURE DISCOURSE IN THE PRACTICE OF MARXIST UTOPIA IMPLEMENTATION - N. G. Mitina (Концепт: философия, религия, культура, 2017)
The article presents the phenomenon of proletariat acting as a social body of Marxist utopian projects. Since socio-cultural reality at any particular historic period is already mature and quite stable structure arisen from social development throughout the course of history, meanwhile the utopia is considered as a phenomenon of the socio-cultural reality, reflecting salient features of the civilization it is based on, it seems possible to reveal the specifics of the Russian proletariat and practical methods of its consciousness formation. The author substantiates the position that specific features of socio-cultural reality caused state Marxism policy formation, emphasizing the need for a prompt transformation of spontaneous proletarian consciousness and its destructive origin into something positive through the development of its self-consciousness creating a positive type of a worker-proletarian. Peculiarities of the Russian reality gave rise to state Marxism formation with a particular focus on a rapid transformation of a spontaneous origin of the working-class movement into the organized class.